2014
DOI: 10.1074/jbc.m114.570838
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of MERTK Receptor Tyrosine Kinase in Epithelial Cancer Cells Drives Efferocytosis in a Gain-of-Function Capacity

Abstract: Background: Overexpression of MERTK tyrosine kinase is observed in many human cancers. Results: MERTK has a potent gain-of-function capacity to stimulate efferocytosis in epithelial cells. Conclusion: When overexpressed, MERTK acts as a preeminent efferocytosis receptor that is targetable by soluble Ig-domain containing TAM receptors. Significance: Our findings provide new mechanistic insight into how MERTK may impinge on tumor progression by enhancing efferocytosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(84 citation statements)
references
References 65 publications
3
80
1
Order By: Relevance
“…4 -6), GAS6 acquires the capability to induce stronger activation of MER; therefore, MER may act as a preferred receptor for GAS6 opsoninzed to PS. This hypothesis is also supported by studies of Nguyen et al (50) demonstrating that ACs only enhance GAS6 induced receptor autophosphorylation in cells expressing MER, but not AXL. This raises an interesting possibility that following PS opsonization, GAS6 switches from preferential AXL binding to MER binding, and, taken further, that MER will function mainly as an efferocytosis receptor that interacts with the surface of ACs, while AXL interacts with un-opsonized GAS6 to stimulate conventional RTK signaling.…”
Section: Discussionsupporting
confidence: 74%
“…4 -6), GAS6 acquires the capability to induce stronger activation of MER; therefore, MER may act as a preferred receptor for GAS6 opsoninzed to PS. This hypothesis is also supported by studies of Nguyen et al (50) demonstrating that ACs only enhance GAS6 induced receptor autophosphorylation in cells expressing MER, but not AXL. This raises an interesting possibility that following PS opsonization, GAS6 switches from preferential AXL binding to MER binding, and, taken further, that MER will function mainly as an efferocytosis receptor that interacts with the surface of ACs, while AXL interacts with un-opsonized GAS6 to stimulate conventional RTK signaling.…”
Section: Discussionsupporting
confidence: 74%
“…MERTK protocol. IHC staining for MERTK was conducted as described (69). Briefly, we followed the same primary antibody protocol as described above, but to increase the sensitivity of MERTK staining we used a biotinylated secondary antibody (goat anti-rabbit IgG; Boster Biotechnology), followed by peroxidase-conjugated streptavidin (SABC; SA1022; Boster Biotechnology).…”
Section: Secondary In Vivo Kinase Screenmentioning
confidence: 99%
“…44 Studies have implicated Mertk to not only be highly elevated in human breast carcinoma samples, but also mediate efferocytosis in macrophages and advance tumor progression through the inhibition of immune checkpoints. 45 In this experiment, MCP-1 depletion resulted in a reduction in both Mertk and CD64 mRNA expression in the mammary gland, and also CD64 mRNA expression in the tumor tissue. These results are consistent with a very recent study in which Fang et al, demonstrated a reduction in the recruitment of macrophages to the tumor microenvironment with targeted MCP-1 gene silencing in a model of TNBC cancer.…”
Section: Discussionmentioning
confidence: 95%